2022
DOI: 10.1159/000522504
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, Treatment, and Outcome of Ocular Hypertension following Intravitreal Steroid Injections: A Comparative Study

Abstract: Purpose: To compare the incidence, risk factors, treatment, and outcomes associated with intravitreal triamcinolone-acetonide (TA) and dexamethasone-implant (Dex) induced ocular hypertension (OHT). Methods: This retrospective study reviewed 1549 TA and Dex administrations in 1075 eyes of 897 patients. Intraocular pressure (IOP) values were monitored for a period of 6-months following intravitreal injection(s) and patients were categorized as steroid-responders (SR): IOP ≥ 21mmHg, and non-responders (NR): IOP ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Comparing the safety profile of DEX with other corticosteroid treatments, such as intravitreal triamcinolone acetonide (IVTA), reveals that DEX is associated with a lower risk of elevated IOP. 15,16 IVTA has been linked to a higher risk of IOP elevation and glaucoma, which has limited its long-term use. 15,16 The findings of the current study, with only two eyes requiring topical AGM, support the notion that DEX may be a safer choice in terms of IOP management.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the safety profile of DEX with other corticosteroid treatments, such as intravitreal triamcinolone acetonide (IVTA), reveals that DEX is associated with a lower risk of elevated IOP. 15,16 IVTA has been linked to a higher risk of IOP elevation and glaucoma, which has limited its long-term use. 15,16 The findings of the current study, with only two eyes requiring topical AGM, support the notion that DEX may be a safer choice in terms of IOP management.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of a second DEX implant at month 6 in 3 patients did not produce an inadvertent bias aiding them to accomplish better therapeutic results. There was no significant increase in IOP after DEX implantation, this outcome being more severe (> 30 mmHg) and significant with the use of triamcinolone compared to dexamethasone [ 47 ]. Considering the relatively small sample size, caution is needed in drawing conclusions regarding the clinically important question being investigated.…”
Section: Discussionmentioning
confidence: 99%
“… 145 Badrinarayanan et al found that 28% of non-glaucomatous eyes developed OHT ≥21 mmHg after triamcinolone-acetonide injection, and 17% of non-glaucomatous eyes that received a DEX implant were GC responders (IOP ≥21mmHg). 146 In a pediatric study, Krag et al found that 56% of children receiving systemic GCs had OHT (net increase in IOP ≥6 mmHg from baseline or a peak IOP ≥21 mmHg). 147 …”
Section: Clinical Science Review Of Gig/giohtmentioning
confidence: 99%
“… 146 In a pediatric study, Krag et al found that 56% of children receiving systemic GCs had OHT (net increase in IOP ≥6 mmHg from baseline or a peak IOP ≥21 mmHg). 147 …”
Section: Clinical Science Review Of Gig/giohtmentioning
confidence: 99%
See 1 more Smart Citation